Budaya Pembelajaran yang Membangun Hakikat Belajar yang Positif - Erlis Sovianti, Salsa; Supriyanto, Ahmad (Humanist Journal, 2025)
A positive learning culture creates an environment where each individual feels supported, inspired, and motivated to learn. This culture encourages appreciation for hard work, perseverance, and the desire to grow in knowledge and skills. The nature of positive learning as a deep understanding of the value of learning as a journey filled with opportunities for growth and discovery. This includes an awareness of the importance of persistence, curiosity, and the ability to overcome obstacles. This article describes the main components of a positive learning culture, including the nature of positive learning, intrinsic motivation, positive rewards and reinforcement, and the learning environment. This study uses a literature study research type with library data collection, reading, recording, and managing research materials. The purpose of this study is to understand the role of learning culture, analyze the influence of the educational environment, and support improvements in the education system. It is important for educators and educational institutions to prioritize the formation of a positive learning culture in order to achieve optimal learning outcomes.